PENGARUH PEMANFAATAN BUKU DIGITAL TERHADAP MINAT LITERASI SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nur Jihan, Adilla; Najmi Laila, Nurul; Linas Ashari, Syifa’ul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of digital book utilization on the literacy interest of fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. Literacy interest is an important foundation in shaping students’ academic success and critical thinking skills, especially in boarding school environments with limited access to printed reading materials. This research employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The research subjects consisted of 38 fifth-grade students. Data were collected through literacy interest tests administered before and after the intervention, as well as questionnaires to support quantitative findings. The data analysis included normality tests, homogeneity tests, descriptive statistics, and paired sample t-tests. The results showed that the data were normally distributed and homogeneous. The descriptive analysis indicated an increase in the average literacy interest score from 47.74 in the pretest to 52.97 in the posttest. Furthermore, the paired sample t-test revealed a significant difference between pretest and posttest results with a significance value of 0.000 (p < 0.05). These findings indicate that the utilization of digital books has a significant positive effect on improving students’ literacy interest. Therefore, digital books can be an effective alternative learning resource to foster literacy culture among elementary school students, particularly in boarding school settings.